Terrorist asset-freezing - continuing flaws in the current scheme - Tomkins, A; Fenwick, H; Lazarus, L (2011)
The Terrorist Asset-Freezing etc Act 2010 came into force on 17 December 2010. The 2010 Act repealed the previous Temporary Provisions Act. This article does not purport to provide comprehensive coverage of the Act; it outlines four main areas of concern that arose in respect of the Draft Terrorist Asset-Freezing Bill and that now arise in respect of the Terrorist Asset-Freezing etc Act 2010. In summary, these are as follows: problems of parliamentary scrutiny relating to the scope of the Act; problems relating to the reasonable suspicion test; problems relating to judicial process; problems relating to ECHR rights. © 2011 Taylor and Francis.